2019
DOI: 10.1093/cid/ciz052
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioidal Meningitis in New York Traced to Texas by Fungal Genomic Analysis

Abstract: A child developed hydrocephalus. Sixteen months later, it was discovered to be a complication of coccidioidal meningitis. The infection’s source was uncertain until genomic analysis of the fungal isolate identified its origin to be a visit to Beeville, Texas. Improved national reporting of cases of coccidioidomycosis might reduce diagnostic delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It is possible that some positive Coccidioides tests, particularly for IgG alone, represent past infection; however, Coccidioides IgG does not persist long after the initial infection and is often used for the diagnosis of recent infections [53,54]. Houston is >100 miles east of areas of Texas with documented locally acquired coccidioidomycosis cases of an outbreak in Beeville, Texas [55]; it is also much farther northeast and much wetter than areas considered highly endemic in West Texas and along the Rio Grande Valley. However, the endemic area for coccidioidomycosis remains poorly defined and may be changing over time.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some positive Coccidioides tests, particularly for IgG alone, represent past infection; however, Coccidioides IgG does not persist long after the initial infection and is often used for the diagnosis of recent infections [53,54]. Houston is >100 miles east of areas of Texas with documented locally acquired coccidioidomycosis cases of an outbreak in Beeville, Texas [55]; it is also much farther northeast and much wetter than areas considered highly endemic in West Texas and along the Rio Grande Valley. However, the endemic area for coccidioidomycosis remains poorly defined and may be changing over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of FDA-approved solutions, rigorous technical requirements, and high start-up costs currently limit the widespread implementation of these assays in clinical laboratories. Outside clinical laboratories, NGS has also been used in outbreak investigations and can reliably link isolates epidemiologically (52,53). Similarly, differentiation between C. immitis and C. posadasii is neither clinically necessary nor possible using most available diagnostic modalities, but it is achievable using molecular approaches like NGS.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…In that study, most patients had either traveled to coccidioidomycosis-endemic regions during the 4 months before symptom onset or visited or previously resided in an endemic region at some point during their lifetimes. Previous studies ( 3 , 15 ) have shown that isolates can be traced to their place of origin by applying current understanding of Coccidioides phylogeography to the increasing number of publicly available genomes. We determined to further investigate the isolates from cases described in the 2016 enhanced surveillance by using genomic epidemiology to empirically evaluate the original findings and identify likely origins of coccidioidomycosis cases in nonendemic regions.…”
mentioning
confidence: 99%